An exploration of the portrayal of the UK soft drinks industry levy in UK national newspapers. Issue 17 (5th December 2020) - Bridge, Gemma; Flint, Stuart W; Tench, Ralph
Abstract: Objective: News media play a role in politics through the portrayal of policies, influencing public and policymaker perceptions of appropriate solutions. This study explored the portrayal of sugar and sugar-sweetened beverage (SSB) taxes in UK national newspapers. Findings aid understanding of the role newspapers play in shaping understanding and acceptance of policies such as the UK Soft Drink Industry Levy (SDIL). Design: Articles discussing sugar or SSB taxes published in six UK national newspapers between 1 April 2016 and 1 May 2019 were retrieved from the LexisNexis database. Articles were thematically analysed to reveal policy portrayal. Setting/Participants: Analysis of UK newspaper articles. Results: Two hundred and eighty-six articles were assessed. Sugar and SSB taxes were discussed across the sample period but publication peaked at SDIL announcement and introduction. Themes were split according to support for or opposition to taxation. Supportive messaging consistently highlighted the negative impacts of sugar on health and the need for complex actions to reduce sugar consumption. Opposing messages emphasised individual responsibility for health and the unfairness of taxation both for organisations and the public. Conclusions: Sugar and SSB taxes received considerable media attention between 2016 and 2019. All newspapers covered arguments in support of and opposition to taxation. Health impacts of excess sugar and the role of the soft drink industry in reducing sugar consumption were prevalent themes, suggesting a joined-up health advocacy approach. Industry arguments were more varied, suggesting a less collaborative argument. Further research should investigate how other media channels portray taxes such as the SDIL.